2020
DOI: 10.3164/jcbn.20-100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics, <i>Bifidobacterium bifidum</i> G9-1, on gastrointestinal symptoms in patients with type 2 diabetes mellitus: study protocol for open-label, single-arm, exploratory research trial (Big STAR study)

Abstract: Metformin is associated with risks of gastrointestinal complica tions in patients with type 2 diabetes. In contrast, probiotic Bifidobacterium bifidum G9 1 (BBG9 1) could improve the symp toms of diarrhea caused by metformin in animal models. Thus, the primary outcome of this study will be the effect of the probiotic BBG9 1 on gastrointestinal symptoms, including diarrhea, in patients with type 2 diabetes who use metformin. This open label, single arm, and exploratory study will examine 40 patients with type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This study was an open-label, single-arm, exploratory study (Effect of Probiotics, Bifidobacteria, on Gastrointestinal Symptoms in Patients with Type 2 Diabetes Mellitus; Open-label, Single-Arm, Exploratory Research [Big STAR study]). The detailed protocol of the Big STAR study has been published previously 18 .…”
Section: Study Design Ethics Approval and Consent To Participatementioning
confidence: 99%
See 1 more Smart Citation
“…This study was an open-label, single-arm, exploratory study (Effect of Probiotics, Bifidobacteria, on Gastrointestinal Symptoms in Patients with Type 2 Diabetes Mellitus; Open-label, Single-Arm, Exploratory Research [Big STAR study]). The detailed protocol of the Big STAR study has been published previously 18 .…”
Section: Study Design Ethics Approval and Consent To Participatementioning
confidence: 99%
“…Based on these findings, we hypothesized that probiotic bifidobacteria could improve gastrointestinal complications, especially constipation and diarrhea, in type 2 diabetes patients treated with metformin; however, there have been no previous studies examining this. Therefore, we carried out the present study to investigate the effects of the probiotic BBG9-1 on the gastrointestinal complications in type 2 diabetes patients treated with metformin 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In a sub-analysis of a previous study [ 15 , 18 ], BBG9-1 oral administration changed the total GSRS score by -0.441 ± 0.499. In the non-treatment period, the change in the total GSRS score was -0.197 ± 0.314.…”
Section: Materials and Methods: Participants Interventions And Outcomesmentioning
confidence: 82%
“…Given the novelty of the topic, studies conducted on human are fewer than animal studies. However, there are several ongoing studies that address the issue [101,102]. One of the first clinical trials that analyzed the effects of adding a prebiotic blend to metformin showed the combination to be significantly better than placebo plus metformin in alleviating the gastrointestinal symptoms associated with metformin intake, and also in lowering FPG levels [103].…”
Section: Human Studiesmentioning
confidence: 99%